Pemanfaatan Limbah Sabut dan Tempurung Kelapa Sawit sebagai Silica Gel - Arbiter Khalida Bramanta; Dewa Made Adit Prasetia; Susilowati Susilowati (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The increase in the area of oil palm in Indonesia also causes an increase in the amount of palm oil waste. Waste in the form of coir and palm shells is thrown away. While the content of silica (SiO2) in both materials is feasible to be utilized. Silica gel is a form of utilization of oil palm coir and shells. The results of X-Ray Fluorescence (XRF) analysis showed that the silica (SiO2) content in palm coir ash was 27.5%, while 36.10% was in palm shell ash. Silica gel is an adsorbent produced by the sol-gel method, namely the formation of a gel derived from precursor compounds. The precursor compound in the formation of silica gel is sodium silicate solution (Na2SiO3) which is produced from the extraction process of coir ash and palm shells using sodium hydroxide (NaOH) solvent. The concentration of NaOH used varied, namely 1, 3, 5, 7, and 9 M. The aging times used for the formation of silica gel also varied, namely 4, 8, 12, 16, and 20 hours. Dry silica gel with the highest quantity of 5.4115 grams was obtained by adding NaOH with a concentration of 9 M and a aging time of 20 hours. While the silica gel which has the most suitable water content and Fourier Transform Infra Red (FTIR) graphic pattern with Kiesel Gel 60 G is silica gel resulting from the addition of 3M NaOH with a aging time of 8 hours. However, the results of the Structural Equation Modeling (SEM) analysis of silica gel showed results that were not in accordance with silica gel in general.